A17 Physiotherapy in HD: Clinical Guidelines and Tips. (17th September 2014) - Busse, M; Quinn, L
Abstract : In 2009, the European Huntington's Disease Network (EHDN) Physiotherapy working group produced a comprehensive Guidance Document and subsequent Clinical Guidelines for physiotherapists in response to the overt need for practice guidelines to guide therapy interventions. At the time, however, there was insufficient literature in support of physiotherapy interventions and approaches to be able to conduct a full, structured evidenced-based review, therefore, physiotherapy expert subgroups were formed to consider the evidence and incorporate consensus as to best practice. Since this time, there has been a growing number of research studies that have evaluated the feasibility and potential benefits of physiotherapy and physical activity interventions for people with Huntington's disease HD, including case studies, feasibility studies of exercise and physiotherapy, and assessment of multidisciplinary inpatient rehabilitation programmes. In this presentation, we will provide an overview of recent studies to date, and discuss their impact on the ongoing clinical validation of Physiotherapy Clinical Guidelines. We will further present the recently developed series of Clinical Tips for Physiotherapists by the EHDN Physiotherapy Working Group, which provide targeted guidance in a readily accessible format. Directions for future research in physical therapies and their potential for symptom management and disease modification across the spectrum of the disease will also be discussed.